1983
DOI: 10.1139/o83-038
|View full text |Cite
|
Sign up to set email alerts
|

In vitro translation of elastin mRNA and processing of the translated products and the signal sequence of elastin a

Abstract: Chick embryo aorta mRNAs were translated in a gel-filtered reticulocyte lysate. The translated products showed two elastin-related proteins (a and b; relative mass approximately 70 000). The translated elastin a protein was separated essentially free of the b protein by centrifugation and sodium dodecyl sulfate (SDS) - polyacrylamide gel electrophoresis. The a protein was then electroeluted from the SDS-polyacrylamide gel and a partial sequence was determined by automated Edman degradation. The NH2-terminal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…There have been few biochemical studies of elastin synthesis, translocation and secretion, but the demonstration that the primary translation product of elastin mRNA has a short hydrophobic N-terminal leader sequence not found in the secreted protein (Karr & Foster, 1981;Davidson et al, 1982;Krawetz et al, 1983) is consistent with the signal hypothesis of Blobel and colleagues (for review see Blobel, 1977). Thus it is postulated that the hydrophobic signal is likely to play a role in protein-membrane recognition, resulting in cotranslational vectorial discharge into the lumen of the endoplasmic reticulum (Sabatini et al, 1982).…”
Section: Discussionmentioning
confidence: 72%
“…There have been few biochemical studies of elastin synthesis, translocation and secretion, but the demonstration that the primary translation product of elastin mRNA has a short hydrophobic N-terminal leader sequence not found in the secreted protein (Karr & Foster, 1981;Davidson et al, 1982;Krawetz et al, 1983) is consistent with the signal hypothesis of Blobel and colleagues (for review see Blobel, 1977). Thus it is postulated that the hydrophobic signal is likely to play a role in protein-membrane recognition, resulting in cotranslational vectorial discharge into the lumen of the endoplasmic reticulum (Sabatini et al, 1982).…”
Section: Discussionmentioning
confidence: 72%
“…Total RNA was isolated from the glands by the method of Harding et al [21] except that the RNA was purified by repeated resuspension and subsequent precipitation with sodium acetate and ethanol [22]. The polyadenylated RNA was prepared from total RNA by oligo(dT)-cellulose chromatography [23,24].…”
Section: Sequence Analysismentioning
confidence: 99%
“…23(0 the mobilities of the higher-Mr peptides in the limited chymotryptic digest show greatest differences and that most of the low-Mr peptides are common to both polypeptides. Evidence that the proposed extra sequence is not the signal peptide which has been lost from tropoelastin b is indicated by studies Krawetz et al, 1983) demonstrating that tropoelastins a and b have similar N-terminal signal-peptide sequences. This latter observation, taken together with the 'peptide mapping' studies in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the elastin mRNA prepared from chick artery cells directs the synthesis of two polypeptides, tropoelastin a and tropoelastin b, when translated in cell-free systems (Foster et al, 1980;Krawetz et al, 1983). When these two closely spaced bands are excised from a polyacrylamide gel and re-electrophoresed individually, they continue to exhibit different electrophoretic mobilities (Fig.…”
Section: Characterization Of Intracellular Tropoelastin Polypeptidesmentioning
confidence: 99%